Substantiation of sources of innovative ideas - Sikorska, Małgorzata; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2021)
Modern methods provide for the possibility of automated implementation of this process using the latest computer technology and using a global information network, which significantly expands the creative potential of man.
Keywords: innovations; projects; stages; intellectual property; enterprises